Effectiveness of Behavioral-Developmental Approach Intervention to Enhancing Verbal and Performance Cognitive Ability on Children with Autism Spectrum Disorders - Ernie Chairuni Siregar; Sunaryo Kartadinata; Zaenal Alimin; Yoga Budhi Santoso (Journal of ICSAR, 2018)
The purpose of this research  to discover the result of an intervention using behavioral- developmental approach to verbal and performance cognitive ability of children with autism spectrum disorders. This study employed a within-group experiment using a single-subject A/B design. The intervention was given to two children  under the age of four by combining learning activities whose curriculum was very well structured with play activities that could stimulate him to interact with others in a more natural setting. The intervention program was given by an educator and parents for 40 hours/ a week in twelve months. The results of the study revealed the behavioral-developmental approach is effective in improving both verbal and performance cognitive ability. this research  are expected to become an alternative intervention  to improve cognitive ability  in children with autism spectrum disorders.